Rendahnya Kemampuan Membaca dan Menulis Siswa Mantang Baru; Identifikasi Faktor Penyebab - Juliana Eka Pratiwi; Dea Junartingsih; Ketryn Oktavia Ginting; Joko Apriadi; Jeremia Sitohang; Abdullah Ziyad Sulthany; Kamirul Kamirul; Jumi Candra; Zahra Vickryana; Jupita Natalia (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the analysis of problems and factors caused by low literacy skills among students, especially in elementary schools. The issue of literacy in Indonesia must be given renewed attention, as literacy greatly influences the growth and development of a generation. Education is very important in a country. Currently, education will become the foundation of a future generation. One of the foundations in question is literacy at an early age. Indonesia can be considered to have a minimal literacy culture. The curriculum plays an important role in ensuring that the learning presented in schools is carried out in a clearer manner. The research described in this article uses descriptive analysis methods based on qualitative data through interviews and observations. The research was conducted at Elementary School 003 in Mantang Baru Village. The research also involved 2nd and 6th grade elementary school students. The results of the study show that the factors causing low literacy skills among students are: (1) communication and guidance from parents and socioeconomic conditions; (2) the educational background of teachers in elementary schools. Based on these findings, the following recommendations can be made: (1) provision of facilities and infrastructure to support literacy, (2) intensive guidance, especially in reading activities at home, (3) the use of reading learning models in the learning process in elementary schools. Therefore, the conclusion that can be drawn is that literacy from an early age is important to optimize children's growth and development, expand language competence, improve critical thinking skills, and prepare them to face further educational challenges. Education and literacy are the main keys to a child's progress because these children will become great people and be able to compete with other children both domestically and abroad.